"Our Kids Aren't Dropping Out; They're Being Pushed Out": Native American Students and Racial Microaggressions in Schools. Issue 1 (2nd January 2017) - Johnston-Goodstar, Katie; VeLure Roholt, Ross
ABSTRACT: Poor graduation rates, truancy rates, and standardized tests results have been presented as indicators of a school crisis among Native American youths. This crisis, however, relies on ahistoric and deficit models of intervention, which imagine academic success as an individual- or family-level phenomenon. Responding to Reyhner's (1991) suggestion to assess the role of schools and teachers in working to push students out of school, we explored the experiences of Native American youths in schools. This article documents findings from a community-based mixed-methods study. It establishes not only the significant prevalence of microaggressions for Native American youths in schools but it also presents the unique discriminatory experiences and aspects of those microaggressions. We suggest that these microaggressions play a role in school climate and push-out and provide suggestions for research, professional development, and social action.